1998
DOI: 10.1542/peds.101.5.892
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Gastroenteritis in Children in Israel

Abstract: Pediatricians in Israel, regardless of country of origin, medical school, or place of practice, are aware of the correct use of ORS but do not follow nutritional practices recommended recently by the AAP. These findings suggest that steps for implementing the guidelines are needed in Israel and most probably worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…The French survey of pediatricians in 2004 showed that 63% allowed rehydration using ORS as compared to 16% of pediatricians in a multi-center European study conducted in 2000, 87% of Israeli pediatricians in 1998, and 30% of US pediatricians in 1991[6–9]. In our survey, 92% of Lebanese pediatricians recommended ORS at the beginning of treatment for rehydration.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The French survey of pediatricians in 2004 showed that 63% allowed rehydration using ORS as compared to 16% of pediatricians in a multi-center European study conducted in 2000, 87% of Israeli pediatricians in 1998, and 30% of US pediatricians in 1991[6–9]. In our survey, 92% of Lebanese pediatricians recommended ORS at the beginning of treatment for rehydration.…”
Section: Discussionmentioning
confidence: 64%
“…Pediatricians who graduated in the last two decades and those working in teaching hospitals and/or in urban areas were more likely to adhere to the AAP guidelines than the other groups. A similar study done in Israel in 1998 showed that 60% of pediatricians followed these guidelines[6]. …”
Section: Discussionmentioning
confidence: 99%
“…Numerous guidelines covering various conditions have been developed in recent years in an effort to provide care based on the best available evidence (12,14). However, implementation of such guidelines is incomplete, may face resistance, and usually requires active measures (14,15). Hence, it is interesting to note that the "Practice Parameter" was readily adopted in the studied hospitals, and had a profound impact on the management of neonatal jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…However, implementation of such guidelines is incomplete, may face resistance, and usually requires active measures (14,15). Hence, it is interesting to note that the "Practice Parameter" was readily adopted in the studied hospitals, and had a profound impact on the management of neonatal jaundice.…”
Section: Discussionmentioning
confidence: 99%